Na Universidade Federal da Paraíba, a Biblioteca Central é a Unidade responsável por receber/validar as produções dos Programas de Pós Graduações do Campus I. A produção é enviada à Biblioteca Central, via autodepósito, como parte dos requisitos para emissão de documentos necessários à composição do processo para emissão do diploma. De forma que inexiste condição ou parcialidade na entrega. Os documentos são definitivos. Tanto a produção depositada pela autoria, quanto o "nada consta" emitido pela Biblioteca Central. Uma vez que temos acesso à produção, passa a ser de responsabilidade da equipe da Biblioteca Central o processamento técnico dos dados para o povoamento do Repositório Institucional. O Termo de Autorização da dissertação foi assinado em 31/10/2024, a aprovação da versão final por parte do orientador data de 06/11/2024, e o povoamento no Repositório ocorreu no dia 06/02/2025. Uma vez a produção disponibilizada na rede mundial de computadores, sob a responsabilidade da Universidade Federal da Paraíba, esse produto foi validado pela Banca, pelo Orientador e poderá, a partir da disponibilidade, ter sido objeto de download e de citações, levando consigo a url da Instituição e, portanto, sendo de responsabilidade da UFPB. Quando acontece de haver necessidade de alteração pontual, a única forma aceita é por meio de Errata. Dito isto, informamos ao senhor Francisco Dennes Rocha Pereira que alterações por ele pretendidas fossem requeridas por Errata, que constará junto com o primeiro documento já disponibilizado à sociedade. Entretanto, o mesmo deseja a substituição da referida dissertação, alegando como motivo principal o fato de “retirar um trecho na fala de um entrevistado que contém a identificação do cargo dele”. - Costa, Roberto Vinicius Antonino da (2024)
Introduction: The diaphragm is the main respiratory muscle, and positive pressure ventilation can affect it, leading to mechanical ventilator dependence and poor clinical outcomes. However, the specific impact of positive pressure on the diaphragm is not yet well understood. Ultrasound stands out as a tool capable of identifying changes in the diaphragm. Objective: To identify the acute effects of positive inspiratory and expiratory pressure applied through CPAP and Bi-level on diaphragmatic thickening in healthy individuals during spontaneous breathing. Additionally, to correlate strength, endurance, and body characteristics with diaphragmatic thickening. Methodology: This is a randomized, cross-over, double-blind clinical trial conducted with individuals aged 18-50 years, excluding volunteers with a history of smoking or any other prior disease. Ultrasound was performed to assess diaphragmatic thickening during spontaneous breathing and with six levels of positive pressure, with the participant in the supine position. Data were analyzed using a Mixed Linear Model and Dunn-Sidak post-test, with correlations performed using the Spearman test. Results: Data were collected from 94 participants during spontaneous breathing and in modes: CPAP (5, 10, and 15 cmH2O) and Bi-level (5, 7, and 10 cmH2O). The obtained data show that the use of CPAP increased diaphragmatic thickening compared to spontaneous breathing, especially at pressures of 10 and 15 cmH2O, while in the Bi-level mode, thickening increased at inspiratory pressure levels of 12 and 15 cmH2O and PEEP of 5 cmH2O. Diaphragmatic thickening during inspiration correlated positively with respiratory muscle strength; similarly, body characteristics were positively correlated with inspiratory and expiratory thickening. However, data on respiratory muscle endurance did not show a correlation with diaphragmatic thickening. Conclusion: The use of CPAP above 5 cmH2O and Bi-level with inspiratory pressure starting at 12 cmH2O and PEEP of 5 cmH2O increased diaphragm thickness. Additionally, respiratory muscle strength and body characteristics positively correlated with diaphragmatic thickening.